A framework for responsive content adaptation in electronic display networks - West, Philip (Rhodes University, Faculty of Science, Department of Computer Science, 2006)
Recent trends show an increase in the availability and functionality of handheld devices, wireless network technology, and electronic display networks. We propose the novel integration of these technologies to provide wireless access to content delivered to large-screen display systems. Content adaptation is used as a method of reformatting web pages to display more appropriately on handheld devices, and to remove unwanted content. A framework is presented that facilitates content adaptation, implemented as an adaptation layer, which is extended to provide personalization of adaptation settings and response to network conditions. The framework is implemented as a proxy server for a wireless network, and handles HTML and XML documents. Once a document has been requested by a user, the HTML/XML is retrieved and parsed, creating a Document Object Model tree representation. It is then altered according to the user's personal settings or predefined settings, based on current network usage and the network resources available. Three adaptation techniques were implemented; spatial representation, which generates an image map of the document, text summarization, which creates a tree view representation of a document, and tag extraction, which replaces specific tags with links. Three proof-of-concept systems were developed in order to test the robustness of the framework. A system for use with digital slide shows, a digital signage system, and a generalized system for use with the internet were implemented. Testing was performed by accessing sample web pages through the content adaptation proxy server. Tag extraction works correctly for all HTML and XML document structures, whereas spatial representation and text summarization are limited to a controlled subset. Results indicate that the adaptive system has the ability to reduce average bandwidth usage, by decreasing the amount of data on the network, thereby allowing a greater number of users access to content. This suggests that responsive content adaptation has a positive influence on network performance metrics.
Keywords: Computer networks; Cell phone systems; Wireless communication systems; Mobile communication systems; HTML (Document markup language); XML (Document markup language)